Badische Anilin- & Soda-Fabrik Zehn Millionen/Fünfhundert Millionen Mark Notgeldschein (Badische Anilin- & Soda-Fabrik, 1923)
This Zehn Millionen/Fünfhundert Millionen Mark Notgeldschein, or ten million/five hundred million Mark emergency money bill, was issued by Ammoniakwerk Merseburg of Badische Anilin- & Soda-Fabrik. Fünfhundert Millionen was printed over the original Zehn Millionen Mark voucher due to rampant hyperinflation. The verso of the company scrip includes the terms of the scrip. This particular voucher was issued by the Ammoniakwerk Merseburg Leuna-werk, or the ammonia works of Merseburg. Paper features a watermark design. As the first fully integrated chemical company in the world, Badische Anilin- & Soda-Fabrik was the world's largest chemical company by the the turn of the twentieth century. Merseburg was the location of Badische Anilin- & Soda-Fabrik's ammonia plant, which also produced syngas, methanol, amines, detergents and catalysts. This German company scrip is an example of the hyperinflation which occurred in Germany after World War One as a result of reparation costs. Due to the devaluation of the Mark, companies began issuing their own currency that employees could use within their company stores. The high value of this currency is indicative of the hyperinflation of the Mark whose value decreased drastically from early 1923 through November 1923.
Keywords: Currency question; Chemical industry; Badische Anilin- & Soda-Fabrik; Corporations; Ammonia industry; Bauman, Robert Joel